Istikhdām Qāmūs al-ʿArabiyyah Baina Yadaik fī Taʿlīm al-Lughah al-ʿArabiyyah bi Maʿhad Al-Khair Cirebon - Antin Lihayati; Ahmad Maghfurin (Alsina : Journal of Arabic Studies, 2021)
This research aims to learn how to use the Al-ʿArabiyyah Baina Yadaik dictionary in teaching Arabic at the Al-Khair Islamic Boarding School - Cirebon, in addition to identifying problems and how to overcome them when using it in education. This is a qualitative descriptive field research that produces data from teachers and students and is collected through observation, interview and documentation. The results indicate: 1) Using the the Al-ʿArabiyyah Baina Yadaik dictionary in education is easier than using any other dictionary. 2) The use of the Al-ʿArabiyyah Baina Yadaik dictionary makes learning Arabic more effective. 3) The lack of existing dictionaries poses problems. Students therefore use the dictionary collectively so that each member of the group can use the Al-ʿArabiyyah Baina Yadaik.* * *Penelitian ini bertujuan untuk mempelajari penggunakan kamus Al-ʿArabiyyah Baina Yadaik dalam mengajar bahasa Arab di Pondok Pesantren Al-Khair-Cirebon, serta mengidentifikasi masalah dan cara mengatasinya dalam pembelaaran. Ini adalah penelitian lapangan deskriptif kualitatif yang datanya bersumber dari guru dan siswa yang dikumpulkan melalui pengamatan, wawancara dan dokumentasi. Hasil Penelitian menunjukkan: 1) Penggunakan kamus Al-ʿArabiyyah Baina Yadaik dalam pembelajaran lebih mudah daripada menggunakan kamus lain. 2) Penggunakan kamus Al-ʿArabiyyah Baina Yadaik membuat pembelajaran bahasa Arab lebih efektif. 3) Kurangnya kamus yang ada menimbulkan masalah. Oleh karena itu siswa menggunakan kamus secara kolektif sehingga setiap anggota kelompok dapat menggunakan kamus Al-ʿArabiyyah Baina Yadaik.